1996
DOI: 10.1002/(sici)1097-0045(1996)7+<48::aid-pros7>3.3.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Review on the simultaneous determination of total prostate‐specific antigen and free prostate‐specific antigen

Abstract: BACKGROUND. The total prostate-specific antigen (t-PSA) in serum measured by PSA assays represents the sum of free (f-PSA) and PSA complexed with al-antichymotrypsin. The f-PSA/t-PSA (F/T) ratio in prostate cancer (PCA) patients is lower than in patients suffering from benign prostatic hyperplasia (BPH). This review summarizes the currrent literature on the clinical relevance of measurement of the F/T PSA ratio. METHODS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…According to some studies, 12,13 the F/T ratio is under the influence of the tumor burden and is shown as a predictor for capsular penetration and harmless cancer. In contrast, there are many observations in which the pre‐operative F/T ratio could not predict whether cancer cells had spread beyond the prostate gland at time of prostatectomy 2,14–16 . As far as we know, reports concerning the F/T ratio in the advanced stage are limited, therefore the present study was aimed at this point and it was shown that the F/T ratio was not affected by tumor burden, indicating independence of the clinical stage.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…According to some studies, 12,13 the F/T ratio is under the influence of the tumor burden and is shown as a predictor for capsular penetration and harmless cancer. In contrast, there are many observations in which the pre‐operative F/T ratio could not predict whether cancer cells had spread beyond the prostate gland at time of prostatectomy 2,14–16 . As far as we know, reports concerning the F/T ratio in the advanced stage are limited, therefore the present study was aimed at this point and it was shown that the F/T ratio was not affected by tumor burden, indicating independence of the clinical stage.…”
Section: Discussionmentioning
confidence: 62%
“…Recently, it was found that the ratio of free‐to‐total PSA (F/T ratio) in the early stage of prostate cancer is lower than that in benign prostatic hyperplasia. Thus this ratio has become a useful index with which the early stage of prostate cancer can be detected in older men 2 . Although negative opinions 3–5 have been voiced on differentiating benign prostatic diseases from prostate cancer among older men with slightly increased t‐PSA (Gray zone, normal upper limit 10 ng/mL) by employing this F/T ratio, there are many others who regard the F/T ratio as a useful marker 6–10 .…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, this scenario does not seem to be plausible because the amount of α‐1‐antichymotrypsin in the blood is 1000‐fold more than that of circulating PSA, thus PSA may be bound easily to α‐1‐antichymotrypsin in the blood irrespective of the presence or absence of malignant tissues. In this context, the F/T ratio is not correlated with stage of prostate cancer and is similar throughout all stages, 9 although the amount of PSA in the blood is greater in advanced stages than that in early stages.…”
Section: Discussionmentioning
confidence: 74%
“…Any damage to prostate, including hyperplasia, adenocarcinoma, cystoscopy, prostatitis, and senility, has been reported to increase the serum level of this antigen; however, this antigen is widely used to diagnose prostate cancer [567]. …”
Section: Introductionmentioning
confidence: 99%